Juupajoen kahdeksankulmainen kirkko : arkkitehtuurirepresentaation kulttuurihistoriallinen konteksti 1800-luvun alun autonomisessa Suomessa - Huikko, Hanna (2023)
The thesis explores the octagonal shape of the Juupajoki Church, built in 1838, within its art and cultural-historical context. The building history and architectural foundations of Juupajoki Church and the bell tower constructed in 1860 are scantily documented in literature relying on archival sources. Originally constructed as a preaching room, there are no known official draw-ings for the church, nor for the bell tower. The church was constructed by local farm owners led by parish carpenter Juho Juhonpoika Salin (1805–1881).